2011
DOI: 10.1016/j.cbi.2011.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase deficiency protects sugar-induced lens opacification in rats

Abstract: Aldose reductase (AKR1B1), which catalyzes the reduction of glucose to sorbitol and lipid aldehydes to lipid alcohols, has been shown to be involved in secondary diabetic complications including cataractogenesis. Rats have high levels of AKR1B1 in lenses and readily develop diabetic cataracts, whereas mice have very low levels of AKR1B1 in their lenses and are not susceptible to hyperglycemic cataracts. Studies with transgenic mice that over-express AKR1B1 indicate that it is the key protein for the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…JNK is thought to be a stress-activated protein kinase (SAPK) that can activate apoptosis [18]. Since AR is the rate-limiting step in the polyol pathway [19], inhibitors of AR have become an important topic of research.…”
Section: Introductionmentioning
confidence: 99%
“…JNK is thought to be a stress-activated protein kinase (SAPK) that can activate apoptosis [18]. Since AR is the rate-limiting step in the polyol pathway [19], inhibitors of AR have become an important topic of research.…”
Section: Introductionmentioning
confidence: 99%
“…A complex pathogenic mechanism underlies diabetic cataract. Though the exact mechanism remains uncertain, a large body of research indicates that aldose reductase (AR) is a key enzyme involved in DC development [2]. In order to reduce diabetic cataract incidence and slow the progression of diabetic cataract in current patients, further understanding of the mechanistic involvement of AR in diabetic cataract development and progression is required.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rate of conversion of sorbitol to fructose is considerably slow and sorbitol does not diffuse out of the cell, hence resulting in its intracellular accumulation [39]. The role of AR in cataractogenesis is further supported by other studies that observed rodents having low or no AR activity are resistant to development of diabetic cataract [40, 41]. Furthermore, Lee et al [42] demonstrated that cataract development in type 2 diabetes mellitus patient may be influenced by polymorphism in AR gene.…”
Section: Discussionmentioning
confidence: 96%